Profile, feelings and participation of family members of homeless drugs users assisted in the Recomeço Família Program - Gilmar Manoel de Barros; Sandra Cristina Pillon; Cláudio Jerônimo da Silva; Ana Lucia de Moraes Horta (Estudos de Psicologia (Campinas))
Abstract Objective To evaluate the sociodemographic profile, the feelings aroused by the use of drugs and the participation of the homeless drug users’ families who sought help in the Recomeço Família Program. Method This is a descriptive, secondary study that used 5,201 records of drug addicts’ family members. We collected sociodemographic data about the family and the addicts, as well as housing, drug use and treatment information and family feelings. Results Family members surveyed were women, adults, with low education, unemployed, and who were parents or guardians (40.9%). The substance users surveyed included 1,477 individuals with low schooling but having a job. Out of this number, 5.4% were homeless, 7.7% young, 6.9% without a partner, 15.4% crack users, with a significant prevalence of women. Family members reported pity, anguish, “pain in the soul” and shame. Conclusion The family members of homeless drug users showed intense suffering requiring formal assistance.